Kajian Etnomatematika Pada Tenun Ikat Motif Tengkawang Desa Tumbak Raya Suku Dayak Keninjal - Anjeli, Meisy; Welly Ferianti, Flesia (FKIP UM Pontianak, 2026)
This study aims to examine the ethnomathematical concepts found in the ikat weaving with the tengkawang motif created by the Dayak Keninjal community in Desa Tumbak Raya. This research used a qualitative approach with an ethnographic method to understand the cultural meanings and mathematical activities involved in the weaving process. The research subjects consisted of traditional weavers and community figures who understand the process of making the tengkawang motif and its philosophical meaning. Data were collected through direct observation, in-depth interviews, documentation, and literature studies. The results of the study show that the tengkawang motif, which is inspired by the fruit of the tengkawang tree, symbolizes fertility, prosperity, and community welfare. In addition to its cultural value, the tengkawang motif also contains several mathematical concepts such as geometric shapes (triangles), symmetry, and repeating patterns. Furthermore, mathematical activities are found in the weaving process, including counting the number of threads (counting), measuring the size of the fabric (measuring), and designing the motif patterns (designing). These findings indicate that the weaving practices carried out by the Dayak Keninjal community indirectly contain mathematical concepts that naturally develop within their cultural activities. Therefore, the ethnomathematical study of the tengkawang motif in ikat weaving can be used as a contextual culture-based mathematics learning resource while also supporting the preservation of local wisdom.